Stealing the Sword Limiting Terrorist Use of Advanced Conventional Weapons - Bonomo, James (RAND Corporation, 2007)
Examines how terrorists make technology choices and how the United States can discourage terrorists' use of advanced conventional weapons. Concludes that the United States should urgently start discussions with key producer nations and also decide on an architecture needed to impose technical controls on new mortar systems that should enter development soon.